PROBLEMS IN INSURANCE OF AGRICULTURAL RISKS AND THE MAIN AREAS OF THEIR SOLUTIONS (Intent Research Scientific Journal, 2023)
Agriculture is considered to be the most vulnerable sector. Agricultural hazards have become the object of extensive scientific research due to their direct impact on the food security of the country and, through this, on the standard of living of the population. Agricultural hazards have their own characteristics. Also, the classification of agricultural risks is typical of sector risks. The article examines two main principles of risk classification and proposes a classification model based on the principle of grouping.